Papillary thyroid carcinoma measuring 1.0 cm or less: an epidemiological and clinicopathological study - El Hag, Imad A.; Tallab, Raghad (Frontiers in Oncology, 2025)
BackgroundThe incidence of papillary thyroid microcarcinoma (PTMC) measuring 1 cm or less has noticeably increased over the past 30 years, particularly among clinically significant subgroups that are diagnosed chiefly preoperatively.MethodsThis retrospective study investigated the rate of occurrence and the pathological high-risk features of PTMC discovered incidentally during thyroidectomies for benign thyroid diseases, as well as those diagnosed preoperatively (non-incidental), in a sample of 1,408 thyroidectomies.ResultsPTMC accounted for 30.5% of all resected malignant thyroid tumors, with 53% being incidental and 47% non-incidental. The incidence of incidental PTMC has increased twofold over the past seven years, from 4.5% to 9.0%, while the incidence of the non-incidental subgroup has increased tenfold, from 0.9% to 9.0%. Compared to incidental cases, non-incidental cases were more likely to affect males, exhibited significantly larger tumors (7.2 mm versus 3.7 mm), and had higher rates of multiplicity (49.4% vs. 23.6%) and bilaterality (36.7% vs. 16.7%). Non-incidental cases also had higher rates of lymph node metastasis (25.9% vs. 4.2%) and greater margin involvement (34.4% vs. 16.7%). Extrathyroidal extension occurred exclusively in approximately 2.5% of the non-incidental cases. The most aggressive PTMC subtype is the tall cell subtype (TCS), followed by the classic subtype, which is observed in 30% and 29% of non-incidental cases, respectively. Follicular subtypes exhibit indolent behavior, as observed in 11% of non-incidental cases. An account of the TCS morphology is also provided.ConclusionThe incidence of PTMC has dramatically increased in the non-screened population. Male sex, tumor size >5 mm, and TCS subtype are risk factors for aggressive behavior.